(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The New Vaisnavism has given emphasis on practical life. One of the main objectives of New Vaisnavism is the combination of the mundane with that of spiritual one. The mundane will be based on righteousness and on which the spirituality will stand. It has opted to establish a casteless society based on equality and fraternity. So, Sri Sri Harichand Thakur a forerunner of New Vaisnavism has discarded the caste system of Hinduism with a paramount voice. The main objective of New Vaisnavism is to uplift the downtrodden and with the same time all-round development of all the people.Mahaprabhu had promised to his mother that He would take birth further as her son. Such an evidence could be found in the"Chaitanya Bhagavat" written by Bridabandas under the heading "Sannyas granartha Gouranger Masthak mundan" in the sixth chapter," Aro dui janma ei sankittanrambhe/ Haiba tomar putra ami abilambe//’. It is said that Mahaprabhu had taken birth at Kheturi as Narattamadas. So, another birth was due. And in the same book He further declared that He would descend to uphold Dharma. "Brahman kuler garba kharba karibare/ Nichjati hoye karba dharmer prachar//" (I shall descend in the lower caste to ward off the boast of the Brahmins.) Mahaprabhu wanted to give everyone the right to chant Harinam irrespective of caste, creed, and religion and of gender. This idea more or less was successful for a time being but the evil of caste system of Hindu Social order engulfed it. It could be found among His devotees in most cases where the Brahmins occupied in the decision making process. Accordingly the reflection of Brahminical idea could be found in the"Chaitanya Charitamrita" by Krishnadas Kabiraj and other books produced after that. The true spirit of the thoughts of Mahaprabhu was hardly found in these writings.